A stepwise degradation of sterically hindered CpCo-cyclobutadiene complexes - Schaefer, Carsten; Gleiter, Rolf; Rominger, Frank (Dalton transactions, 2004)
Sterically hindered CpCo stabilized cyclobutadiene complexes 4 were oxidized by ceric ammonium nitrate to yield the dinitratocobalt complexes 5. The thermolysis of 5a and the reaction of 5a with tert-butyl isocyanide as well as NaBH4 is reported.
Gesehen am 23.10.2020